Automation Technique Design Classification of Technological Objects - Kulmuratova Aliya Janabay qizi (Scientific Trends, 2023)
The development of artificial intelligence is rapid and the integration of artificial intelligence with automation has begun change work clothes. The article describes the methodology of using artificial intelligence methods to create an integrated environment for computer-aided design components based on the classification, integration and configuration of technological objects. This describes the formation of structures based on the object-oriented approach, methods setting up an integrated environment and organizing unified information empty space. The methodology of organizing the configuration of system components and the interaction of structured components, obtaining the final structured architecture, is shown to be aimed at solving the problem. Using this method for a formal description of project operations and the use of genetic algorithms optimization of the operational parameters of the process and the design of the technological machine are described. Companies and businesses are focusing on referrals Advanced Artificial Intelligence with automation progressions to take advantage of the new the pinnacle of skill and excellence. Paper gives an artificial picture intelligence and automation, and how it exposes both to the audience artificial intelligence and automation are intertwined and how they can be more when they work together and can have a competitive advantage.
Keywords: Autonomic computing, modernization, algorithms, automation industry, technological machines, information system, automated system.